Kualitas audit PENGARUH PENGALAMAN AUDITOR TERHADAP KUALITAS AUDIT DI KANTOR AKUNTAN PUBLIK - Mardianti Mashanafi (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2022)
This study aims to determine the effect of responsibility, work experience on auditorperformance in public accounting firms. This research method uses Literature Reviewwith a research sample of 10 journals sourced from Google Scholar Publication media witha duration of literature review, for 10 years, starting from 2013 to 2022. The results of thisresearch are from analyzing articles that related to the influence of auditor experience onaudit quality in the public accounting firm shows that the auditor's experience has a morepositive effect on audit quality in public accounting firms. In this study there are still manyshortcomings, including deficiencies in the research method used in this study because itonly uses the literature review method, without conducting direct analysis or field work.This research is expected to be a reference for further studying the effect of workexperience on audit quality in public accounting firms.